Distribution of Species of the Genus Astragalus L. in Kyrgyzstan by Habitat Type - Mamatkulov, Orozbay; Kolanov, Orunbek; Attokurov, Kursantbek; Erkebaeva, Zhanan (Research in Ecology, 2025)
According to literary data, there are 189 species of the genus Astragalus that inhabit the territory of Kyrgyzstan. The distribution of species of the genus Astragalus (Fabaceae) was studied by taking into account their occurrence in soil-climatic and relief types of plant habitats in the mountainous territories of Kyrgyzstan. The materials were collected during organized research expeditions to natural areas of plant habitats. The occurrence of species was studied by well-known methods. As a result of such analysis we have made the following conclusions for the first time: in the flora of Kyrgyzstan there are 189 species of the genus Astragalus, they are representatives of 7 subgenera of this genus; species occur in 24 types of plant habitats with soil and relief features, taking into account the altitudinal regularity of taxa distribution in mountain phytocenoses; subgenuses and specific species characterized by broad, smallest and intermediate sizes of habitats were identified; groupings of plant habitat types on the territory of Kyrgyzstan characterized by the largest, smallest and intermediate indicators on the number of subgenuses and species of the genus Astragalus were identified. The botanical description of each species has been supplemented with new information about the species as a taxonomic unit. The materials of our work can be successfully used in the field of systematics, evolution and ecology of plants.